PENGARUH WORK DESIGN, ORGANIZATIONAL CULTURE, WORK COMPETENCE TERHADAP EMPLOYEE PERFORMANCE MELALUI WORK MOTIVATION - Arga Putra; Medina Nilasari (FEB Universitas Sam Ratulangi Manado, 2023)
The global cosmetics market experienced a fairly deep contraction in 2020. This was in line with the world's sluggish economic conditions due to the Covid-19 pandemic. As a result of the decline in cosmetic sales, many employees were laid off, so the number of unemployed increased from the previous year. Employees who have poor performance for the company will experience termination of employment by the company. This study analyzes the effect of Work Design, Organizational Culture, and Work Competence on Employee Performance through Work Motivation. The population of this research is cosmetic Sales Promotion Girls in Jakarta. The sampling technique used purposive sampling with a total sample of 185. The data collection technique used a questionnaire that had been tested for validity and reliability. Data analysis technique using structural equation modeling (SEM) based on partial least squares (PLS). The results of this study indicate that: work design has a negative effect on work motivation and employee performance, organizational culture has a positive effect on work motivation, organizational culture has a positive effect on employee performance, work competence has a negative effect on work motivation, work competence has a positive effect on employee performance, work motivation has a negative effect on employee performance, work design has a positive effect on employee performance through work motivation, organizational culture has a negative effect on employee performance through work motivation, and work competence has a positive effect on employee performance through work motivation.